A framework to evaluate public green spaces with an emphasis on recreational values for sustainable urban and rural areas: A systematic review and content analysis - Amirmohammad Ghavimi; Frank Schuessler; Roland Pesch (Heliyon)
Though numerous studies acknowledge the critical role played by green spaces (GS) in bolstering sustainability in various dimensions, a majority of these investigations primarily center on the ecological aspect and urban environments. Due to the multifaceted benefits of GSs, different categories and expectations of these spaces can be identified across disciplines. Hence, no single method exists for evaluating the success of GSs in promoting sustainability due to the multifaceted benefits and variety of expectations. This study provides a framework for evaluating public green spaces (PGS) holistically based on sustainability discourse, specifically including rural and transitional rural-urban areas, with a focus on GS's recreational values. Employing a systematic review of 130 publications sourced from Web of Science, Scopus, and Google Scholar and ensuing content analysis, we identified and elaborated on 14 distinct qualities, including accessibility, connectedness, responsiveness, variety of activity, social interactions, facilities, safety and security, spaciousness, biodiversity, perceptual value, aesthetic value, and symbolic value. The interrelationships among these identified qualities are also elucidated through the content analysis.These qualities can be utilized as a novel approach to evaluate the efficiency of PGSs in promoting sustainability.